Edukasi Manajemen Stres terhadap Kesehatan Mental Remaja dalam Pembelajaran Online di Masa Pandemi - Indriastuti, Devi; Caturini, Endang; Insiyah, Insiyah (Jurnal Empathy Pengabdian Kepada Masyarakat, 2023)
Background: Adolescents are a group vulnerable to experiencing stress, especially during online learning during the COVID-19 pandemic. Changes in the learning system, limited social interaction, and academic pressure lead to psychological disorders such as anxiety, difficulty concentrating, and a decrease in learning motivation. This community service activity aims to improve the mental health of adolescents through stress management education at SMK Negeri 1 Sambi Boyolali. Methods: The activity method was carried out using an online counselling and training approach involving 66 twelfth-grade students. The activity was conducted in two sessions over 10 days, with guidance from lecturers and students. The material provided includes understanding stress, positive self-talk techniques, deep breathing relaxation, and study time management. Evaluation was conducted using the Self Reporting Questionnaire (SRQ-29) before and after the activity. Results: The results of the activity show an increase in participants' knowledge and skills in recognising and managing stress. The average stress score decreased significantly, with a 58.5% increase in positive coping abilities after training. Most participants also reported feeling calmer, more confident, and more motivated in their learning. Conclusion: This activity proves that stress management education is effective as a promotive and preventive effort in maintaining the mental health of adolescents, and can be implemented as a model for psychological guidance in secondary schools.